Ruptured Ectopic Pregnancy - Valentina Park; Shannon Toohey (eScholarship Publishing, University of California, 2016)
History of present illness: A 21-year-old female presented with sudden onset suprapubic abdominal pain associated with dysuria. The patient also experienced near syncope during bowel movements three times three days ago without falling or losing consciousness. She denied fever, nausea, and vomiting. She stated that she was five weeks pregnant by last menstrual period. She had an ultrasound a few weeks before that showed no intrauterine pregnancy, but she had not followed up for additional testing. Significant findings: The patient's serum beta-hCG was 5,637 mIU/mL. The transvaginal ultrasound showed an empty uterus with free fluid posteriorly in the pelvis and Pouch of Douglas (00:00). A 4.5 cm heterogeneous mass was visible in the left adnexa concerning for an ectopic pregnancy (00:10). Discussion: Ectopic pregnancies are a leading cause of maternal morbidity and mortality, as well as decreased fertility.1,2 Differentiating between an ectopic pregnancy and a normal early pregnancy may be difficult, since ultrasound and quantitative beta-hCG may show inconclusive results.3,4 Patients who have used fertility treatment may further complicate the picture because they are at risk for heterotypic pregnancies.5 Ectopic pregnancies most commonly implant in the fallopian tube, but may alternatively implant in the ovary, cervix, abdomen, or uterine cornua.4 Ultrasonography may show an empty uterus, adnexal mass, pelvic free fluid, or an extra-uterine gestational sac, yolk sac, and/or embryo.6 Treatment options for ectopic pregnancy include surgery or methotrexate.2,4 Some patients may be candidates for close outpatient surveillance if the diagnosis is unclear or in very limited cases for early, non-ruptured ectopic pregnancies.2,4